On the loading mechanism of ssDNA into carbon nanotubes. Issue 70 (31st July 2015) - Shen, Jia-Wei; Tang, Ting; Wei, Xiao-Hong; Zheng, Wei; Sun, Tian-Yang; Zhang, Zhisen; Liang, Lijun; Wang, Qi
<x xml:space="preserve">Abstract</x> The loading mechanism and dynamics of ssDNA oligomers into single-walled carbon nanotubes was investigated. The binding free energy is in the order A-zigzag SWNT (24, 0) > T-zigzag SWNT (24, 0) > A-armchair SWNT (14, 14) > T-armchair SWNT (14, 14).